MR-Guided Functional Neurosurgery: Laser Ablation and Deep Brain Stimulation. Issue 3 (June 2018) - Boone, Christine E.; Wojtasiewicz, Teresa; Moukheiber, Emile; Butala, Ankur; Jordao, Ligia; Mills, Kelly A.; Sair, Haris; Anderson, William S.
Abstract : Abstract: Intraoperative magnetic resonance imaging (iMRI) is increasingly implemented for image-guided procedures in functional neurosurgery. iMRI facilitates accurate electrode implantation for deep brain stimulation (DBS) and is currently an alternative method for DBS electrode targeting. The application of iMRI also allows for greater accuracy and precision in laser-induced thermal therapy (LITT). The expanding use of functional neurosurgical procedures makes safety and feasibility of iMRI important considerations, particularly in patients with comorbidities or complex medical histories. We review here the applications of iMRI and discuss its safety, feasibility, and limitations in functional neurosurgery. To motivate discussion of this topic, we also present a 52-year-old patient with an implanted cardioverter-defibrillator (ICD) who successfully underwent iMRI-guided DBS electrode implantation for advanced Parkinson disease (PD). Neither iMRI nor the passage of electrical current through the implanted DBS electrodes demonstrated detectable interference in ICD function. This case demonstrates that, even in complex clinical contexts, iMRI is a promising tool that merits further exploration for procedures requiring highly accurate and precise identification of target structures.